FRI0282 Post-Treatment Short-Term Changes in Needle Electromyography among Patients with Polymyositis and Dermatomyositis and Their Clinical Usefulness: A Retrospective Study. (15th July 2016) - Kawasumi, H.; Katsumata, Y.; Ito, E.; Nishino, A.; Kawaguchi, Y.; Yamanaka, H.
Abstract : Background: There is no established single outcome measure of muscle manifestations in polymyositis (PM) and dermatomyositis (DM) although there are partially validated preliminary definitions of improvement by the International Myositis Assessment & Clinical Studies Group (IMACS). They are core set measures including Manual Muscle Testing (MMT), muscle-associated enzymes such as creatine kinase (CK), and so on. Needle electromyography (EMG) is useful in the diagnosis of PM/DM. However, the degree and time course of changes in its findings after treatment and their associations with other measures remain elusive. Objectives: We aimed to study post-treatment short-term changes in needle EMG among patients with PM/DM and their clinical usefulness. Methods: Patients were included in the present study when they met all these criteria: 1) fulfill the Bohan and Peter classification criteria for PM/DM; 2) were administered to our university hospital for the treatment of muscle manifestations of PM/DM from 2008 through 2015; 3) received needle EMG before and after treatment. Needle EMG was performed by a single experienced electromyographer/neurologist in all the patients. The data of findings of needle EMG, MMT, serum CK levels, and other demographic and clinical information were retrospectively collected. The following findings of needle EMG were transformed into semiquantified relative frequencies on 0–7 point scale: fibrillation potential (Fib), positive sharp wave (Pos), low-amplitude motor unit potential (MUP) (Low), short-duration MUP (Short). MMT was assessed in 10 muscles on 0–5 point scale and their sum scores with maximum of 50 were used. Treatment was determined by physician preference in each individual. Results: Ultimately, 24 patients were included in the present study, and 17 and 10 patients received needle EMG at 4 and 8 weeks after treatment, respectively: 3 patients received at both 4 and 8 weeks after treatment. Fib was detected in 23 patients, and Pos, Low, and Short were detected in all the patients before treatment. Fib, Pos, Low, and Short improved in 59%, 65%, 29%, and 24% of the patients at 4 weeks, and in 90%, 90%, 100%, and 90% of the patients at 8 weeks, respectively. When assessed by Wilcoxon signed-rank tests, Fib and Pos significantly improved at 4 weeks, and all of the needle EMG findings improved at 8 weeks ( p <0.05 in each comparison). Although MMT scores and CK levels also significantly improved, their improvement did not significantly agree with the improvement of needle EMG findings except for Fib and Pos and CK levels at 8 weeks. Conclusions: The present study showed that electrical activity in muscle recorded at rest (Fib and Pos) and during voluntary movement (Low and Short) significantly improved at as early as 4 and 8 weeks after treatment, respectively. It is also suggested that needle EMG findings can serve as different outcome measure from MMT and CK in PM/DM. Disclosure of Interest: None declared